Of Books and Beasts; A Cryptozoologist’s Library by Matt Bille - Champagne, Bruce (Journal of Scientific Exploration, 2022)
Opportunities for the peer-reviewed presentation of specifically cryptozoological subjects are currently limited to the Relict Hominoid Inquiry and Journal of Scientific Exploration. As a result, books not only have an important role in providing historical information and more current data and theory but are also preferable over other sources as the reader can evaluate the value of a book by the author’s approach and sources. There are many cryptozoological titles but not they are not equal in contribution.